(3ZSjd GdCehGd (B:s (3LQjeI GdYUQ (B/s - (3GdbShS, QeRj fLjHs ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2002)
(3JYQja LQjeI ZSd GdCehGd(B- (3GdWHjYI GdbGfhfjI dLQjeI ZSjd GdCehGd(B- (3eQGMd LQjeI ZSjd GdCehGd(B- (3CfeGW hhSGFd ZSjd GdCehGd(B- (3eUGOQ GdCehGd ZjQ GdTQYjI(B- (3eDTQGJ ZSjd GdCehGd(B-(3GdLghO GdOhdjI aj ecGaMI ZSjd GdCehGd(B- (3GdYhGed GdJj JLYd GdOhdI gOaG dZSjd GdCehGd(B- (3GdEQgGH GdOhdj hZSjd GdCehGd(B- (3ebJQMGJ decGaMI ZSjd GdCehGd(B- (3HYV GdeUWdMGJ GdeSJYedI aj ZSjd GdCehGds
Keywords: (3LQGFe GdGNJdGSs; (3LQGFe GdCehGds; (3LQGFe GdJgQjHs